Shielding in Wales: National Identity and Everyday Experiences - BETHAN HIER (2023)
At the start of the COVID-19 pandemic, people were advised to ‘shield’ by the UK and Welsh Governments if they had compromised immune systems and were thus at higher risk of a severe reaction to the virus. Some people did not leave their homes for several months, the effects of which have been well documented by news stories and medical research. Social research has begun to document the effects of the pandemic, but less attention has been paid to the effects of shielding specifically. This research therefore focuses on people’s experiences of shielding in Wales during the first lockdown of the COVID-19 pandemic in 2020 and aims to shed light on how this isolation affected people’s daily lives and their relationship with the nation. It analyses responses from a questionnaire that Amgueddfa Cymru – National Museum Wales ran between May and October 2020 and semi-structured interviews with people who shielded who are living in South Wales. The themes discussed in this thesis are politics and national identity, everyday experiences and vulnerability, and through these themes, it explores the political and social dimensions of shielding. This thesis argues that, alongside the common biological conceptions of it, shielding is a political and social endeavour, and it affected people’s relationship with various aspects of their identity, including their national identity and sense of vulnerability, and the effects of it can be seen in people’s everyday lives and have lasted beyond the timeframe of the first lockdown and shielding period. People who shielded encountered borders at various scales including personal and national borders. It is important to hear these personal narratives that are often overlooked in official discussions of coronavirus policy.